Durability properties of lightweight self-consolidating concrete developed with three types of aggregates. (1st March 2016) - Lotfy, Abdurrahmaan; Hossain, Khandaker M.A.; Lachemi, Mohamed
Highlights: Lightweight self-consolidating concrete (LWSCC) with three types of aggregates. Evaluate LWSCC resistance to elevated temperatures and acid attack. Evaluate LWSCC resistance against freeze–thaw and salt scaling. Confirm potential of proposed LWSCC mixtures for construction applications. Abstract: The durability properties of lightweight self-consolidating concrete (LWSCC) using three types of lightweight aggregates: furnace slag (FS), expanded clay (EC), and expanded shale (ES) is presented. LWSCCs exhibited superior fire resistance in terms of residual strength showing formation of no major cracking (only visible hairline cracks)/spalling after exposure to elevated temperatures of up to 900 °C for a duration of 1.5 h. Salt-scaling resistance was also found to be adequate and primarily dependent on the aggregate quality and associated properties. LWSCC mixtures showed enhanced resistance against sulfuric acid attack due to proper formation of the cementitious paste matrix. However, non-air entrained LWSCC mixtures were unable to withstand severe freezing and thawing cycles.